Influencing factors of eosinophilia in peripheral blood of maintenance hemodialysis patients and its relationship with prognosis - Shu-min Bao; Qiao-jing Liang; Guo-juan Zhang (Linchuang shenzangbing zazhi)
ObjectiveTo explore the influencing factors of eosinophilia in peripheral blood of maintenance hemodialysis patients and examine its relationship with prognosis.MethodsFrom January 1 to January 31， 2018， 114 MHD patients at dialysis center of our hospital were retrospectively selected and divided into two groups of A （>5%） and B （<5%） according to the proportion of eosinophil. The inter-group differences in baseline profiles and laboratory tests were analyzed. They were followed up for 45 months. Logistic model was utilized for examining the factors related to all-cause endpoint events and receiver operating characteristic （ROC） curve for analyzing the predictive efficacy of elevated eosinophil ratio on all-cause endpoint events.ResultsSignificant inter-group differences existed in gender， coronary heart disease， cardiac function grade Ⅲ/Ⅳ， high-sensitivity C-reactive protein， dialysis adequacy （Kt/V）， pre-dialysis calcium （Ca）， ferritin， parathyroid hormone （iPTH） and all-cause endpoints （P<0.05）. After adjusting for various confounding factors， Logistic analysis revealed a significant correlation between all-cause endpoints and elevated proportion of eosinophils （P=0.03， 95%CI 1.013-1.281）. The area under the curve （AUC） of predicting all-cause endpoint was 68% with a sensitivity of 68% and a specificity of 74.6%.ConclusionInflammatory status， iPTH and pre-dialysis calcium are the influencing factors of elevated eosinophil ratio. And elevated eosinophil ratio is an independent risk factor for all-cause endpoint events in MHD patients.